Citizen science to monitor the establishment and spread of a biological control agent: the case of Pareuchaetes pseudoinsulata (Lepidoptera, Erebidae) for the control of Chromolaena odorata (Asteraceae) in South and South-East Asia - Matthew J. W. Cock; Michael D. Day; Rachel L. Winston (CABI Agriculture and Bioscience)
Abstract Pareuchaetes pseudoinsulata Rego Barros (Lepidoptera, Erebidae) has been deliberately released in six countries in South and South-East Asia as a biological control agent for Chromolaena odorata (L.) R.M. King & H. Rob. (Asteraceae). To date, the scientific literature has records of establishment in only four of these countries: India, Indonesia, Malaysia and Sri Lanka. Georeferenced and dated images shared by citizen scientists on the iNaturalist.org platform were used to assess the establishment and spread of P. pseudoinsulata. Adding to our existing knowledge, it was found that P. pseudoinsulata is established in Thailand and Vietnam and has spread to China (Yunnan and Hainan provinces), Cambodia and West Malaysia (Penang). We discuss the value of using citizen science to track the establishment and spread of weed biological control agents, using P. pseudoinsulata as an example.